IMPLEMENTATION OF SMART INDONESIA PROGRAMME (PIP) AT SMP NEGERI 11 BANDAR LAMPUNG - Hinfa Mosshananza (DEMOKRASI, 2021)
Based on Presidential Instruction No. 7 of 2014 on the Implementation of Prosperous Family Savings Programme, Smart Indonesia Programme, and Healthy Indonesia Programme to Build Productive Families. The purpose of this research is to find out the Implementation of the Smart Indonesia Programme Policy in SMP Negeri 11 Bandar Lampung. This research method uses a descriptive qualitative approach. The results showed that the implementation of the Smart Indonesia Programme policy on the aspect of communication in the form of socialization between the Education Office and the School that has been done now is quite effective. The obstacle in communication problems is that there are still student guardians who do not understand the benefits and procedures for proposing to get the help of the Smart Indonesia Programme. In terms of resources both employees and equipment in supporting the Smart Indonesia Programme both in the Education Office and in SMP Negeri 11 Bandar Lampung is adequate, but for some schools, there are still obstacles to the unstable internet network. On the disposition aspect that the implementation of duties and functions of the department and schools related to this Programme has been implemented well to the beneficiaries of the Smart Indonesia Programme in Bandar Lampung City. However, the School's supervision of the use of aid funds by students receiving the Smart Indonesia Programme is still not optimal because the school does not know with certainty the usefulness of the funds used. While aspects of the bureaucratic structure of the implementation of the Smart Indonesia Programme policy have been implemented, but there are also still obstacles, namely the school is still difficult to register students who desperately need the Programme.Keyword : Implementation, Smart Indonesia Programme